Hot carriers in semiconductor nanostructures : physics and applications - Shah, J. (Jagdeep) (Academic Press, 1992)
Nonequilibrium--hot--charge carriers play a crucial role in the physics and technology of semiconductor nanostructure devices. This book--one of the first on the topic--discusses fundamental aspects of hot carriers in quasi-two-dimensional systems and the impact of these carriers on semiconductor devices. The work will provide scientists and device engineers with an authoritative review of the most exciting recent developments in this rapidly moving field. It should be read by all those who wish to learn the fundamentals of contemporary ultra-small, ultra-fast semiconductor devices. Key Features * Topics covered include * Reduced dimensionality and quantum wells * Carrier-phonon interactions and hot phonons * Femtosecond optical studies of hot carriers * Ballistic transport * Submicron and resonant tunneling devices.